A SULTAN OF TERNATE, MUDAFFAR SJAH, AND THE LOCAL POLITICS CONSOLIDATION DURING THE NEW ORDER ERA FROM 1966 TO 1998 - rustam hasim; Syawal Abdulajid; Mohtar Kamisi (Universitas Hasanuddin, 2021)
This paper defines the political strategy of the 48th Sultan of Ternate, Mudaffar Sjah, in reorganizing his power base after the death of the 47th Sultan of Ternate, Iskandar Djabir Syah, in 1975. This paper emphasizes two strategies of the elite of the Sultanate of Ternate to maintain their political existence in the local political sphere. The first is associated with government parties: During the era of the Soeharto government, the elite of the sultanate took political decisions to support the government party, the GOLKAR. The support of the Sultanate of Ternate to the GOLKAR Party was understood as an accommodating strategy and maintained in authoritarian and centralist power. The accommodating approach aimed to survive the destruction as occurred in the Soekarno government and be able to utilize the resources possessed by the force of the New Order.